Neonatal jaundice and its association with sepsis, birth trauma, and prolonged labor in Ethiopia: A systematic review and meta-analysis - Bezawit Adane; Melaku Yalew; Elsabeth Addisu; Mastewal Arefaynie; Kefale Mitiku; Yitbarek Wasihun; Tilahun Degu Tsega; Mahider Awoke; Tezera Asfaw; Bereket Kefale; Yitayish Damtie; Natnael Kebede (Elsevier, 2024)
Background: No comprehensive nationwide evidence exists regarding neonatal jaundice in Ethiopia. Hence, this study aimed to determine the pooled prevalence of neonatal jaundice and explore its relationship with sepsis, birth trauma, and prolonged labor in Ethiopia. Methods: The systematic review and meta-analysis adhered to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. It encompassed both published and grey literature, identified through suitable keywords across various databases: PubMed, Cochrane Library, PsycINFO, Hinari, and Google Scholar. Data extraction was conducted using Microsoft Excel, and meta-analysis was performed using STATA/MP 16. To assess heterogeneity and publication bias, I2 and Egger test statistics were employed, respectively. Sensitivity analysis and subgroup analysis were also carried out. Results: This systematic review and meta-analysis comprised nine articles involving a collective participant count of 6282. The pooled prevalence of neonatal jaundice in Ethiopia was determined to be 31.59 % [95 % CI: 20.02, 43.17]. Notably, the presence of neonatal sepsis [AOR = 1.91, 95 % CI: 1.24-2.96)] and prolonged labor [AOR = 2.03, 95 % CI: 1.29-3.20] exhibited significant associations with neonatal jaundice. Conclusions: The prevalence of neonatal jaundice in Ethiopia surpassed studies conducted outside the country. Notably, neonatal sepsis and prolonged labor showed significant associations with neonatal jaundice. Consequently, stakeholders such as the government and healthcare providers should prioritize interventions aimed at reducing the incidence of neonatal sepsis within routine healthcare services. Additionally, healthcare professionals need to remain vigilant for prompt management of prolonged labor and timely treatment of neonatal sepsis, especially if the issue has already emerged.